Preparation method of homogeneous prebaked anode taking waste anode as aggregate
By using the waste anode as aggregate, combined with dry mixing, wet mixing, vacuum belt pressure medium frequency vibration forming and roasting processes, a homogeneous pre-baked anode was prepared, solving the problem of uneven coating caused by the differences in the surface structure of the calcined petroleum coke. , significantly improves the performance and quality of the prebaked anode and realizes the recycling of resources.
Patent Information
- Application Number
- CN202411591758.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-18
AI Technical Summary
In the existing prebaked anode production, the microstructure and pore structure of the surface of the calcined petroleum coke are largely different, resulting in uneven coating and impregnation of coal asphalt, resulting in uneven baked products, and reducing the quality of the prebaked anode.
The waste anode is used as aggregate, and a homogeneous prebaked anode is prepared through dry mixing, wet mixing, vacuum belt pressure medium frequency vibration forming and baking processes. This method dry-mixed waste anode particles aggregate, calcined coke powder and grinder tailwind powder in a specific proportion, added coal asphalt for wet mixing, and then carried out vacuum belt pressure medium frequency vibration forming and roasting.
Significantly improves the overall performance of the prebaked anode, improves the interface bonding strength, improves the bulk density, reduces the air permeability and resistivity, extends the service life, and realizes the recycling of resources, which is in line with green production and circular economy. Requirements.
Smart Images

Figure CN119462153A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of prebaked anodes, and in particular relates to a method for preparing a homogeneous prebaked anode using waste anodes as aggregates. Background Art
[0002] At present, the main raw materials for the production of prebaked anodes include aggregates (calcined petroleum coke) and binders (high-temperature modified coal tar), which are prepared through processes such as batching, mixing, kneading, vibration molding and roasting. Due to the wide range of sources of raw petroleum coke, there are significant differences in the surface microstructure and pore structure of the calcined petroleum coke produced, which makes the wettability and permeability of coal tar to calcined petroleum coke vary greatly during the kneading process, resulting in uneven coating and infiltration, which further leads to uneven pores and structural defects in the green body during the roasting process, reducing the production quality of prebaked anodes. Therefore, how to improve the microstructural defects on the surface of aggregates and improve the homogeneous coating and infiltration of coal tar to aggregates is a key issue in improving the quality of prebaked anodes.
[0003] Waste anodes are the residual parts of the prebaked anodes at the end of the electrolysis cycle in the electrolytic refining process. At present, they are mainly used for melting and recasting into anodes. There are also waste anodes for other uses. For example, copper waste anodes can be added to the converter as cold materials, and can also be used as raw materials for making copper sulfate; nickel waste anodes can be used to make electrolytes to supplement nickel ions. However, studies have shown that the amount of waste anodes added in the production of carbon anodes should not exceed 25%, otherwise it will affect the quality of the anodes, so the recycling capacity of waste anodes is limited. Compared with calcined coke, the structure of the waste anodes used as aggregates in the production process of prebaked anodes is more stable, and the surface is coated with the same asphalt carbonization products, so that the surface has a rich pore structure, and the surface roughness and microscopic pore structure between different particles are highly consistent, which is conducive to the uniform coating and infiltration of asphalt on aggregates, thereby improving the interfacial bonding strength of the roasted products. In addition, the use of waste anodes can not only reduce carbon emissions, but also reduce production costs and realize the recycling of resources.
[0004] CN106757162A discloses an aluminum electrolysis prebaked anode and its production process. The raw materials of the aluminum electrolysis prebaked anode include 82% to 86% of ingredients and 14% to 18% of binder by weight, wherein the ingredients include 80% to 84% of calcined petroleum coke, 14% to 16% of residual anode and 2% to 4% of cathode milling flour by weight, and a prebaked anode product with low resistivity is obtained. CN114349512A discloses a method for preparing a low carbon slag prebaked anode for aluminum electrolysis, wherein calcined coke, modified asphalt, residual anode and additives are kneaded, wherein the weight ratio of calcined coke, modified asphalt and residual anode is 100:15-25:5-15, and a kneaded material is obtained. The process prepares high-quality prebaked anodes, which effectively reduces the amount of slag falling from the electrolytic cell anode. It can be seen that the current process uses the prebaked anode residual as an auxiliary material of the aggregate, and a small amount of addition is added, and the ability to recycle the residual anode is limited.
[0005] Under existing technical conditions, the prebaked anode production industry basically uses calcined petroleum coke or a mixture of calcined petroleum coke and graphitized coke as raw materials, and forms them through traditional vibration methods. The density of the formed body is low, the risk of internal defects is high, the risk of roasting quality is high, and the incidence of internal cracks is high. At present, the prebaked anode production industry has no technical solution to fully utilize the superior performance of waste anodes as aggregates and innovate production processes to prepare homogeneous prebaked anodes. Summary of the invention
[0006] Based on the above technical background, the present invention provides a method for preparing a homogeneous prebaked anode with waste anode as aggregate, wherein the waste anode granular aggregate, calcined coke powder and mill tail wind powder are dry mixed by weight percentage of 70-80%, 15-20% and 2-8% respectively, wherein the waste anode granular aggregate includes 36-40% of 6# material with a particle size of 6-3mm, 32-36% of 3# material with a particle size of 3-1mm after washing oil pretreatment, and 24-28% of 1# material with a particle size of 1-0.075mm, and then wet mixed, vacuum belt pressure medium frequency vibration molding, and roasting are performed to obtain a homogeneous prebaked anode. The preparation method of the present invention significantly improves the overall performance of the prebaked anode and effectively extends the service life of the prebaked anode; secondly, the large-scale utilization of waste anodes reduces the mining and production of new materials, reduces damage to the environment, and meets the requirements of green production and circular economy.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions:
[0008] A method for preparing a homogeneous prebaked anode using waste anodes as aggregates is characterized in that the waste anode particle aggregates prepared by pretreatment, calcined coke powder and mill tail wind powder are dry-mixed in weight percentages of 70-80%, 15-20% and 2-8% respectively, and then wet-mixed with coal tar, vacuum-pressured medium-frequency vibration molding and roasting are performed to obtain a homogeneous prebaked anode.
[0009] The above preparation method comprises the following specific steps:
[0010] (1) Preparation of waste anode granular aggregate: crushing and screening the waste anode to obtain 6# material, 3# material, and 1# material, and pretreating the 3# material before mixing to obtain waste anode granular aggregate;
[0011] (2) dry mixing: the spent anode aggregate particles, calcined coke powder and mill tail wind powder obtained in step (1) are mixed evenly to obtain a mixture;
[0012] (3) Wet mixing: adding three types of coal tar pitch with low, medium and high softening points to the mixture obtained in step (2) in sequence and kneading them for equal periods of time to obtain an anode paste;
[0013] (4) Molding: adding the anode paste obtained in step (3) into a preheated mold and subjecting it to vacuum belt pressure medium frequency vibration molding, and after demolding and cooling, obtaining a high-density prebaked anode green block;
[0014] (5) Calcination: The pre-baked anode green block obtained in step (4) is calcined to obtain a homogeneous pre-baked anode.
[0015] Furthermore, the waste anode particle aggregate in step (1) comprises, by weight percentage: 36-40% of 6# material with a particle size of 6-3mm, 32-36% of 3# material with a particle size of 3-1mm, and 24-28% of 1# material with a particle size of 1-0.075mm; the pretreatment is: spraying washing oil on the 3# material while stirring until the surface of the 3# material is completely covered with the washing oil, and drying at 250-270°C.
[0016] Furthermore, the calcined coke powder in step (2) is a calcined coke powder with a particle size of 0.075-0.054 mm; the mill tail wind powder is: ultrafine powder with a particle size of less than 0.054 mm produced during the processing of the calcined coke dust powder in the mill; the mixing temperature is 150-160°C, and the mixing time is 10-15 min.
[0017] Furthermore, the total amount of coal tar added in step (3) is 13-17% of the total weight of the anode paste, and the amounts of low, medium and high softening point coal tars added are the same; the core control indicators of the coal tar are volatile matter ≤55%, coking value ≥57%, toluene insoluble matter 26%-28%, quinoline insoluble matter ≤9%, and wettability 1.5-1.7; the softening points of the low, medium and high softening point coal tars are 100±2°C, 105±2°C, and 108±2, respectively; the kneading temperature is 160-170°C, and the different coal tars are kneaded for equal time after addition, and the total kneading time is 10-15min.
[0018] Furthermore, in step (4), the mold preheating temperature is 145-155°C; the vacuum belt pressure medium frequency vibration parameters are: vacuum degree ≤ 0.07MPa, vibration frequency 30-50Hz, specific pressure 1.1-1.3kg / cm 2 The vibration time is 60-120s, until the density of the prebaked anode green block is ≥1.73g / cm 3 .
[0019] Furthermore, the control parameters of the roasting process in step (5) are: gradually increasing the temperature from room temperature to 1050-1150°C, the heating rate in the low-temperature stage below 300°C is 8-13°C / h, the heating rate in the high-temperature stage of 300-1150°C is 45-55°C / h, and after constant temperature roasting at 1050-1150°C for 70-80h, the temperature is lowered to 180-220°C before being taken out of the furnace.
[0020] The preparation method of the present invention adopts waste anodes with multiple particle size ratios as the main raw material, fully utilizes the characteristics that the surface of the waste anode has rich pore structure and the surface roughness and microscopic pore structure consistency between different particles are high, promotes the uniform coating and infiltration of asphalt into aggregates, improves the interface bonding strength of the prebaked anode, increases the volume density of the prebaked anode, reduces the air permeability, and enhances the mechanical strength; and uses washing oil to pretreat the waste anode particles, aiming to enhance the active components on its surface and promote the formation of bonding bridges, thereby improving the overall quality of paste kneading; secondly, a small amount of mill tail wind powder is added to improve the bulk density and fluidity of the aggregate; three types of coal tar with low, medium and high softening points are added for kneading, the first addition enhances the wettability of the anode paste, the second addition enhances its bonding performance, and the third addition enhances the coking rate; vacuum belt pressure medium-frequency vibration molding effectively inhibits the internal cracking of the prebaked anode green block; after the improvement and design of the above process, a homogeneous prebaked anode with superior performance is obtained, and the preparation process flow chart and internal structure schematic diagram of the homogeneous prebaked anode are shown as follows Figure 1 , 2 shown.
[0021] Beneficial effects:
[0022] (1) By recycling waste anodes and useless mill tail wind powder, the mining and production of new materials are reduced, the production cost is effectively reduced, and the requirements of green production and circular economy are met.
[0023] (2) The homogeneous prebaked anode obtained by the raw material formulation, kneading and vacuum compaction processes provided by the present invention has a prebaked anode finished product density of 1.637 g / cm 3, which is better than the prebaked anode prepared by the traditional calcined petroleum coke vibration process; it can effectively reduce the resistivity, air permeability, CO2 reactivity, and thermal expansion coefficient of the prebaked anode, among which the resistivity is significantly better than the resistivity of the national standard first-class product after calcination, which can be controlled between 45-50μΩ.m; it improves the flexural strength, compressive strength, and dynamic elastic modulus. The preparation method of the present invention significantly improves the overall performance of the prebaked anode and effectively extends the service life of the prebaked anode, which is of great significance for the quality improvement, efficiency enhancement, and high-quality development of the electrolytic aluminum industry. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The process flow chart of preparing homogeneous prebaked anode;
[0025] Figure 2 Schematic diagram of the internal structure of the homogeneous prebaked anode;
[0026] Figure 3 Observation diagram of the surface morphology of prebaked anodes under different processes; wherein a is the prebaked anode green block and prebaked anode obtained by comparative example 5 (i.e. conventional process), and b is the prebaked anode green block and homogeneous prebaked anode obtained by embodiment 1 (i.e. the present invention). DETAILED DESCRIPTION
[0027] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be specifically described below in conjunction with the embodiments of the present invention. The described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0028] Example 1
[0029] A method for preparing a homogeneous prebaked anode using waste anode as aggregate, the method specifically comprising the following steps:
[0030] (1) Preparation of waste anode granular aggregate: crushing and sieving the waste anode to obtain 6# material with a particle size of 6-3 mm, 3# material with a particle size of 3-1 mm, and 1# material with a particle size of 1-0.075 mm, and spraying washing oil on the 3# material while stirring until the surface of the 3# material is completely covered with washing oil, and then drying at 260° C. for standby use; and mixing the 6# material, the 3# material, and the 1# material in weight percentages of 38%, 34%, and 28%, respectively, to obtain waste anode granular aggregate;
[0031] (2) Dry mixing: firstly, the calcined coke is crushed and sieved to obtain calcined coke powder with a particle size of 0.075-0.054 mm, and then the tail wind powder of the mill with a particle size of less than 0.054 mm generated during the processing of the calcined coke dust powder in the mill is collected; finally, 75% of the waste anode particle mixture obtained in step (1), 20% of the calcined coke powder and 5% of the tail wind powder of the mill are mixed in a kneader at 150° C. for 10 minutes to obtain a mixture;
[0032] (3) Wet mixing: adding 5% of the total weight of the anode paste to the mixture obtained in step (2) of low-softening-point coal tar pitch with a softening point of 100°C, 5% of the medium-softening-point coal tar pitch with a softening point of 105°C, and 5% of the high-softening-point coal tar pitch with a softening point of 108°C in order by weight percentage, and kneading the different coal tar pitches at 160°C for 5 minutes to obtain a uniformly kneaded anode paste; wherein the core control indicators of the coal tar pitch are: volatile matter ≤55%, coking value ≥57%, toluene insoluble matter 26%-28%, quinoline insoluble matter ≤9%, and wettability 1.5-1.7;
[0033] (4) Molding: The anode paste obtained in step (3) was placed in a mold at a temperature of 150°C for scraping, and vacuum was drawn before vibration. The vacuum degree was controlled to be 0.07 MPa and the specific pressure was 1.2 kg / cm 2 Start vibration under vacuum and hammer pressure, adjust the vibration frequency to 40Hz, vibration time to 80s, and when the set density reaches ≥1.73g / cm 3 Then stop vibrating, demould and cool to room temperature to obtain high-density pre-baked anode green blocks;
[0034] (5) Calcination: The prebaked anode green block obtained in step (4) is calcined according to the following calcination parameters: gradually increasing the temperature from room temperature to 1100°C, with a heating rate of 8-13°C / h in the low-temperature stage below 300°C and a heating rate of 45-55°C / h in the high-temperature stage of 300-1100°C. After constant temperature calcination at 1100°C for 76 hours, the temperature is reduced to 200°C and taken out of the furnace to obtain a homogeneous prebaked anode.
[0035] Example 2
[0036] A method for preparing a homogeneous prebaked anode using waste anode as aggregate, the method specifically comprising the following steps:
[0037] (1) Preparation of waste anode granular aggregate: crushing and sieving the waste anode to obtain 6# material with a particle size of 6-3 mm, 3# material with a particle size of 3-1 mm, and 1# material with a particle size of 1-0.075 mm, and spraying washing oil on the 3# material while stirring until the surface of the 3# material is completely covered with washing oil, and then drying at 260° C. for standby use; and mixing the 6# material, the 3# material, and the 1# material in weight percentages of 37%, 36%, and 27%, respectively, to obtain waste anode granular aggregate;
[0038] (2) Dry mixing: firstly, the calcined coke is crushed and sieved to obtain calcined coke powder with a particle size of 0.075-0.054 mm, and then the tail wind powder of the mill with a particle size of less than 0.054 mm generated during the processing of the calcined coke dust powder in the mill is collected; finally, 80% of the spent anode granular aggregate obtained in step (1), 15% of the calcined coke powder and 5% of the tail wind powder of the mill are mixed in a kneader at 150° C. for 10 minutes to obtain a mixed material;
[0039] (3) Wet mixing: adding 5% of the total weight of the anode paste to the mixture obtained in step (2) of low-softening-point coal tar pitch with a softening point of 100°C, 5% of the medium-softening-point coal tar pitch with a softening point of 105°C, and 5% of the high-softening-point coal tar pitch with a softening point of 108°C in order by weight percentage, and kneading the different coal tar pitches at 160°C for 5 minutes to obtain a uniformly kneaded anode paste; wherein the core control indicators of the coal tar pitch are: volatile matter ≤55%, coking value ≥57%, toluene insoluble matter 26%-28%, quinoline insoluble matter ≤9%, and wettability 1.5-1.7;
[0040] (4) Molding: The anode paste obtained in step (3) was placed in a mold at a temperature of 150°C for scraping, and vacuum was drawn before vibration. The vacuum degree was controlled to be 0.065 MPa and the specific pressure was 1.3 kg / cm 2 , start vibration under vacuum and hammer pressure, adjust the vibration frequency to 50Hz, vibration time to 80s, and when the set density reaches ≥1.73g / cm 3 Then stop vibrating, demould and cool to room temperature to obtain high-density pre-baked anode green blocks;
[0041] (5) Calcination: The prebaked anode green block obtained in step (4) is calcined according to the following calcination parameters: gradually increasing the temperature from room temperature to 1100°C, with a heating rate of 8-13°C / h in the low-temperature stage below 300°C and a heating rate of 45-55°C / h in the high-temperature stage of 300-1100°C. After constant temperature calcination at 1100°C for 76 hours, the temperature is reduced to 200°C and taken out of the furnace to obtain a homogeneous prebaked anode.
[0042] Comparative Example 1
[0043] The difference between this comparative example and Example 1 is that the raw material mixture for preparing the prebaked anode is different.
[0044] A method for preparing a prebaked anode, the specific steps are as follows:
[0045] (1) Preparation of mixed material: crushing and sieving calcined petroleum coke to obtain calcined coke particles of different particle sizes, and putting the calcined coke particles into a dry mixer according to the following weight percentages: 6# material: 28%, 3# material: 26%, 1# material: 21%, powder: 20%, and ultrafine powder: 5%, and dry mixing at 150° C. for 10 minutes to obtain a mixed material;
[0046] (2)-(4) are the same as steps (3)-(5) of Example 1 to obtain a prebaked anode.
[0047] Comparative Example 2
[0048] The difference between this comparative example and Example 1 is that the 3# aggregate used to prepare the prebaked anode is not pretreated with washing oil.
[0049] A method for preparing a prebaked anode, the specific steps are as follows:
[0050] (1) Preparation of waste anode granular aggregate: crushing and sieving the waste anode to obtain 6# material with a particle size of 6-3 mm, 3# material with a particle size of 3-1 mm, and 1# material with a particle size of 1-0.075 mm, and mixing the 6# material, 3# material, and 1# material in weight percentages of 38%, 34%, and 28%, respectively, to obtain waste anode granular aggregate;
[0051] (2)-(5) The same steps (2)-(5) as in Example 1 are carried out to obtain a prebaked anode.
[0052] Comparative Example 3
[0053] The difference between this comparative example and Example 1 is that the vibration forming process for preparing the prebaked anode is different.
[0054] A method for preparing a prebaked anode, the specific steps are as follows:
[0055] (1)-(3) are the same as steps (1)-(3) in Example 1;
[0056] (4) Molding: The anode paste obtained in step (3) is placed in a mold at a temperature of 150° C. for scraping, and a conventional vibration molding method is used with a vibration frequency of 50 Hz, an amplitude of 0.03 mm, and a weight pressure of 1.2 kg / cm 2 , the vibration time is 150s, demoulding and cooling to room temperature to obtain pre-baked anode green blocks;
[0057] (5) Calcination: The prebaked anode green block obtained in step (4) is calcined according to the following calcination parameters: the temperature is gradually increased from room temperature to 1100°C, the heating rate in the low temperature stage below 300°C is 8-13°C / h, and the heating rate in the high temperature stage of 300-1100°C is 45-55°C / h. After constant temperature calcination at 1100°C for 76 hours, the temperature is reduced to 200°C and taken out of the furnace to obtain a prebaked anode.
[0058] Comparative Example 4
[0059] The difference between this comparative example and Example 1 is that the coal tar pitch used to prepare the prebaked anode is different.
[0060] A method for preparing a prebaked anode, the specific steps are as follows:
[0061] (1)-(2) are the same as (1)-(2) in Example 1;
[0062] (3) Wet mixing: adding coal tar pitch equivalent to 15% of the total weight of the anode paste to the mixture obtained in step (2) by weight percentage at one time, mixing at 160° C. for 15 minutes, and obtaining a uniformly kneaded anode paste; wherein the core control indicators of the coal tar pitch are: softening point of 107° C., ash content of 0.09%, volatile content of 56.19%, coking value of 56.82%, toluene insoluble matter of 28.35%, quinoline insoluble matter of 8.51%, and wettability of 1.79;
[0063] (4)-(5) are the same as (4)-(5) in Example 1.
[0064] Comparative Example 5
[0065] The difference between this comparative example and Example 1 is that the mixture, coal tar pitch and molding process of the prebaked anode are all different.
[0066] A method for preparing a prebaked anode, the specific steps are as follows:
[0067] (1) Preparation of mixed material: crush and screen the calcined petroleum coke to obtain calcined coke particles of different particle sizes, put the calcined coke particles into a dry mixer according to the following weight percentages: 6# material: 28%, 3# material: 26%, 1# material: 21%, powder: 20%, and ultrafine powder: 5%, and dry mix them at 150° C. for 10 minutes to obtain a mixed material;
[0068] (2) Wet mixing: adding 15% of the total weight of the anode paste to the mixture obtained in step (1) by weight, and mixing at 160° C. for 15 min to obtain a uniformly kneaded anode paste; wherein the core control indicators of the coal tar are: softening point of 107° C., ash content of 0.09%, volatile content of 56.19%, coking value of 56.82%, toluene insoluble matter of 28.35%, quinoline insoluble matter of 8.51%, and wettability of 1.79;
[0069] (3) Molding: The anode paste obtained in step (2) is placed in a mold at a temperature of 150° C. for scraping, and a conventional vibration molding method is used with a vibration frequency of 50 Hz, an amplitude of 0.03 mm, and a weight pressure of 1.2 kg / cm 2 , the vibration time is 150s, demoulding and cooling to room temperature to obtain pre-baked anode green blocks;
[0070] (4) Calcination: The prebaked anode green block obtained in step (3) is calcined according to the following calcination parameters: the temperature is gradually increased from room temperature to 1100°C, the heating rate in the low temperature stage below 300°C is 8-13°C / h, and the heating rate in the high temperature stage of 300-1100°C is 45-55°C / h. After constant temperature calcination at 1100°C for 76 hours, the temperature is reduced to 200°C and taken out of the furnace to obtain a prebaked anode.
[0071] Test example
[0072] (1) Observation of the surface state of the prebaked anode
[0073] The surface state of the homogeneous prebaked anode obtained in Example 1 and the prebaked anode obtained in Comparative Example 5 (conventional process) was observed and analyzed. Figure 3 It can be seen that the green block and homogeneous prebaked anode obtained in Example 1 have uniform surface texture, no obvious pores and structural defects, and are significantly better than the green block and prebaked anode obtained in Comparative Example 5.
[0074] (2) Homogeneous prebaked anode performance test
[0075] The homogeneous prebaked anode obtained in Example 1-2 and the prebaked anode obtained in Comparative Example 1-5 were tested for performance, and the specific testing method was tested in accordance with the standard YS / T 63.9-2012 "Testing Methods for Carbon Materials for Aluminum". The performance test indicators are shown in Table 1:
[0076] Table 1 Prebaked anode performance test comparison table
[0077]
[0078] As shown in Table 1, the homogeneous prebaked anode obtained by the raw material formulation, kneading and vacuum compaction processes provided by the present invention achieves a prebaked anode finished product density of 1.637 g / cm3 , which is better than the prebaked anode prepared by the traditional calcined petroleum coke vibration process; it can effectively reduce the resistivity, air permeability, CO2 reactivity, and thermal expansion coefficient of the prebaked anode, among which the resistivity is significantly better than the resistivity of the national standard first-class product after calcination, and can be controlled between 45-50μΩ.m; it improves the flexural strength, compressive strength, and dynamic elastic modulus. The preparation method of the present invention significantly improves the overall performance of the prebaked anode and can effectively extend the service life of the prebaked anode.
Claims
1. A method for preparing a homogeneous prebaked anode using waste anode as aggregate, characterized in that: The waste anode particle aggregate prepared by pretreatment, calcined coke powder and mill tail wind powder are dry-mixed according to the weight percentage of 70-80%, 15-20% and 2-8% respectively, and then wet-mixed with coal tar, vacuum-pressured medium-frequency vibration molding and roasting are carried out to obtain a homogeneous prebaked anode.
2. The method for preparing a homogeneous prebaked anode according to claim 1, characterized in that: The method comprises the following steps: (1) Preparation of waste anode granular aggregate: crushing and screening the waste anode to obtain 6# material, 3# material, and 1# material, and pretreating the 3# material before mixing to obtain waste anode granular aggregate; (2) dry mixing: the spent anode aggregate particles, calcined coke powder and mill tail wind powder obtained in step (1) are mixed evenly to obtain a mixture; (3) Wet mixing: adding three types of coal tar pitch with low, medium and high softening points to the mixture obtained in step (2) in sequence and kneading for equal periods of time to obtain an anode paste; (4) Molding: adding the anode paste obtained in step (3) into a preheated mold and subjecting it to vacuum belt pressure medium frequency vibration molding, and after demolding and cooling, obtaining a high-density prebaked anode green block; (5) Calcination: The pre-baked anode green block obtained in step (4) is calcined to obtain a homogeneous pre-baked anode.
3. The preparation method according to claim 2, characterized in that: The waste anode particle aggregate in step (1) comprises, by weight percentage: 36-40% of 6# material with a particle size of 6-3mm, 32-36% of 3# material with a particle size of 3-1mm, and 24-28% of 1# material with a particle size of 1-0.075mm.
4. The preparation method according to claim 2, characterized in that: The pretreatment in step (1) is as follows: spraying washing oil on the 3# material while stirring until the surface of the 3# material is completely covered with the washing oil, and drying at 250-270°C.
5. The preparation method according to claim 2, characterized in that: The calcined coke powder in step (2) is a calcined coke powder with a particle size of 0.075-0.054 mm; the mixing temperature is 150-160° C., and the mixing time is 10-15 min.
6. The preparation method according to claim 2, characterized in that: The mill tail wind powder in step (2) is: ultrafine powder with a particle size of less than 0.054 mm generated during the processing of the calcined coke dust powder in the mill.
7. The preparation method according to claim 2, characterized in that: The total amount of coal tar pitch added in step (3) is 13-17% of the total weight of the anode paste, and the amount of low, medium and high softening point coal tar pitch added is the same; the core control indicators of the coal tar pitch are volatile matter ≤55%, coking value ≥57%, toluene insoluble matter 26%-28%, quinoline insoluble matter ≤9%, and wettability 1.5-1.7; the softening points of the low, medium and high softening point coal tar pitches are 100±2°C, 105±2°C, and 108±2, respectively; the kneading temperature is 160-170°C, and the different coal tar pitches are kneaded for equal time after addition, and the total kneading time is 10-15min.
8. The preparation method according to claim 2, characterized in that: The mold preheating temperature in step (4) is 145-155°C; the medium-frequency vibration parameters of the vacuum belt pressure are: vacuum degree ≤ 0.07MPa, vibration frequency 30-50Hz, specific pressure 1.1-1.3kg / cm 2 The vibration time is 60-120s, until the density of the prebaked anode green block is ≥1.73g / cm 3 .
9. The preparation method according to claim 2, characterized in that: The control parameters of the roasting process in step (5) are: gradually heating from room temperature to 1050-1150°C, the heating rate in the low-temperature stage below 300°C is 8-13°C / h, the heating rate in the high-temperature stage of 300-1150°C is 45-55°C / h, and after constant temperature roasting at 1050-1150°C for 70-80h, the temperature is lowered to 180-220°C before being taken out of the furnace.
10. A homogeneous prebaked anode prepared according to the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Prebaked anode for aluminum electrolysis and production process thereof
CN106757162A
Preparation method of low-carbon-residue prebaked anode for aluminum electrolysis
CN114349512A
Method for preparing carbon anodes for aluminum through residual anodes
CN106222700A
Carbon product vacuum-pumping vibration efficient forming method
CN112009010A
Aggregate pretreatment prebaked anode and preparation method thereof
CN116041064A